2020
DOI: 10.1038/s41598-020-65709-3
|View full text |Cite
|
Sign up to set email alerts
|

Cold climate adaptation is a plausible cause for evolution of multicellular sporulation in Dictyostelia

Abstract: Unicellular protozoa that encyst individually upon starvation evolved at least eight times into organisms that instead form multicellular fruiting bodies with spores. the Dictyostelia are the largest and most complex group of such organisms. They can be subdivided into 4 major groups, with many species in groups 1-3 having additionally retained encystment. To understand fitness differences between spores and cysts, we measured long-term survival of spores and cysts under climatemimicking conditions, investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…As mentioned earlier, the fossil-calibrated phylogeny of Amoebozoa sets the split between the two major branches of Dictyostelia at 0.52 billion years ago (Figure 2), following the global glaciations known as "snowball earth" [51,52]. Combined, these observations suggest that Dictyostelium sporulation in multicellular fruiting bodies was an adaptation to cold climate [23].…”
Section: Ecological Advantages Of Spores Over Cysts: Increased Dispermentioning
confidence: 58%
See 4 more Smart Citations
“…As mentioned earlier, the fossil-calibrated phylogeny of Amoebozoa sets the split between the two major branches of Dictyostelia at 0.52 billion years ago (Figure 2), following the global glaciations known as "snowball earth" [51,52]. Combined, these observations suggest that Dictyostelium sporulation in multicellular fruiting bodies was an adaptation to cold climate [23].…”
Section: Ecological Advantages Of Spores Over Cysts: Increased Dispermentioning
confidence: 58%
“…By examining the survival curves of cysts and spores from 29 Dictyostelids from all major groups, Lawal and co-authors showed that spores withstand frost better than cysts, with group 4 spores being most frost-resistant. In non-freezing temperatures survival rates between spores and cysts were not significantly different [23]. Comparative ultrastructural studies of spores and cysts revealed that spores are more compacted than cysts and have well-defined three-layered walls, while cyst walls consist of only one or two layers.…”
Section: Ecological Advantages Of Spores Over Cysts: Increased Dispermentioning
confidence: 85%
See 3 more Smart Citations